An Influence Safety Technician Flight Aircraft on Workload - Ratri Ratri (Budapest International Research and Critics University, 2021)
Flight safety is identical to the performance of aircraft. To have a standard of flight safety, an aircraft needs good maintenance to achieve the best performance. An aircraft technician should have a good qualification as stated in ICAO. They have a complex job that usually creates a high workload which is harmful to flight safety. This research aims to analyze the workload experienced by the aircraft technician at Lion Mentari Airline and in which interval, to examine factors affecting the workload value and to examine the influence of workload value on flight safety. The aircraft technician workload was analyzed using Subjective Workload Assessment Technique (SWAT) software. The data was taken from 50 aircraft technicians of Lion Mentari Airline inline maintenance. They were asked to rank the Sort Card according to their perception of mental workload. There are combination levels that should be made in order from the lowest to the highest. The mental workload combination consists of Time Load (T), Mental Effort Load (E), and Psychological Stress Load (S).The result shows that the workload experienced by the aircraft technician at Lion Mentari Airline is 61.44 which is in the interval of Over Load. From three dimensional workloads, Time Load (T) has the highest value (percentage) than Mental Effort Load (E) and Psychological Stress Load (S) which is 40.67% (participant 1-25) and 41.48% (participant 26-50). It shows that the workload concern of the Aircraft technician at Lion Mentari Airline in line maintenance is on Time Load. The high workload will make high error risks and the probability to produce accidents is high. The errors can be reduced or prevented by identifying causes which most frequently occur (Dirty Dozen) and making barriers (Safety Nets/ Safeguard) to prevent the accident by using the Swiss Cheese Model and ICAO’s SHELL Model Approach.